2010
DOI: 10.1016/j.jecp.2010.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of reading development in deaf children: A 3-year longitudinal study

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. The development of reading ability in a group of deaf children was followed over a three year period. 29 deaf children, aged 7-8 years old at the first assessment, participated in the study and every 12 months they were given a battery of literacy, cognitive and language based tasks. Earlier vocabulary and speechreading skills predicted longitudinal growth in reading achievement. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
155
2
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 148 publications
(184 citation statements)
references
References 46 publications
17
155
2
10
Order By: Relevance
“…Language delay has in fact been described as a hallmark of deafness (Musselman, 2000). In two longitudinal studies of reading development in deaf children from mixed language backgrounds (Kyle & Harris, 2010;, we found that vocabulary and speechreading were the strongest predictors of later reading ability. Other researchers have also found speechreading to be a strong correlate of reading in deaf children (e.g.…”
Section: Deaf Children's Use Of Phonology During Readingmentioning
confidence: 61%
See 4 more Smart Citations
“…Language delay has in fact been described as a hallmark of deafness (Musselman, 2000). In two longitudinal studies of reading development in deaf children from mixed language backgrounds (Kyle & Harris, 2010;, we found that vocabulary and speechreading were the strongest predictors of later reading ability. Other researchers have also found speechreading to be a strong correlate of reading in deaf children (e.g.…”
Section: Deaf Children's Use Of Phonology During Readingmentioning
confidence: 61%
“…Hanson & Fowler, 1987;Kyle & Harris, 2006;Leybaert & Alegria, 1993). Kyle and Harris (2010) reported a strong relationship between phonological awareness and reading in deaf children; however, it is important to note that the direction of this relationship was in fact from reading to phonological awareness. This finding is important as it suggests that deaf children's phonological awareness skills develop as a consequence of learning to read rather than being a precursor of reading ability as is typically found in hearing children (see also Musselman, 2000;Goldin-Meadow & Mayberry, 2001).…”
Section: Deaf Children's Use Of Phonology During Readingmentioning
confidence: 98%
See 3 more Smart Citations